Sinope's Changing Epochs: a Colony's Adaptation to a Common Paphlagonian Past. - Ching-Yuan Wu (2025 AIA/SCS Joint Annual Meeting, January 2nd to January 5th, 2025, 2025)
A few colonies in the Latin West (Augusta Emerita, Johnston 2017: 56-57 fn. 202-203; Abascal 2002: 284) and the Greek East (e.g. Philippi AE 1932, 21; briefly Samos IG XII,6 1:187 l. 8-11) used the annus coloniae, the year when the colony was founded, as their standard time-reckoning formula on inscriptions and perhaps other media as well. The list may include the Roman colony of Sinope, which coin issues carried legends such as C(olonia) F(elix) I(ulia) an(no) followed by (and later on simply with) Latin numerals (e.g. RPC I 2110, II 715). Curiously, since the 17th century, numismatists have observed two epochs on Sinope’s Roman period issues (e.g. Hardouin 1689: 140). There was the epoch of 45 BCE, likely the annus coloniae (e.g. RPC III 1229), as it coincided with reports of a Caesarian colony (Strab. 12.3.11). Then there was the epoch of 70 BCE (e.g. RPC VI 6501), seemingly replacing the earlier epoch, but only from the early third century onwards (Kubitschek 1908: 68-71; Magie 1950: 342 no. 42).  Changing epochs was not a rare phenomenon in Anatolia, but known examples changed an earlier epoch for a later one, apparently to adapt to new circumstances, such as an imperial victory or visit (Leschhorn 1993: 439-541), and count years from a new beginning. Sinope, however, changed the epoch that was supposedly linked to the year of its colonial foundation to an earlier epoch that coincided with Lucullus’ “liberation” of Sinope from Mithridatid control. This suggests that Sinope was adapting to new circumstances that required the adaptation of an historical epoch. It is not the beginning per se, but a recaliberation of municipal history. While historical developments of Roman Sinope is not well documented in extant literary sources, and epigraphic evidence is scarce, this paper wishes to take two approaches to assess the problem of Sinope’s changing epochs. The first approach is to consider Sinope’s time-reckoning tradition. The era system that was prevalent in northern Anatolia and elsewhere during the first three centuries CE had a strong Hellenistic tradition. In this view, there may be more nuance – 45 BCE can be the annus coloniae, but it was reflecting a recent change in the city’s history, not an overhaul of the city’s established time-reckoning system, perhaps based on the Seleucid era (found on ceramic stamps, Saprykin & Fedoseev 1999: 135-143). This approach removes the Roman symbolism attached to the 45 BCE, and opens up additional possibilities for interpretation. The second approach considers the epoch of 70 BCE regionally. This epoch was primarily used at Amastris, but also attested at Abonuteichos. Both cities were described by Roman authors as prosperous in their own ways (e.g. Luc. Alex. 9, 25; Plin. Ep. 10.98). Both cities also began to issue 3 to 4 units of local bronze coinage from the reign of Trajan onwards, including the 6-assaria, associated with economic prosperity (Zajac 2023: 30-32, Tab. 1a). Epigraphic and numismatic evidence further suggest that Amastrians were mobile across the Black Sea and the Aegean, some even serving as koinon officials of Bithynian and other regional koina (Marek 2003: 63-67). There is the possibility that Sinope changed its epoch to adhere to regional time-reckoning norms set by more dominant peers. Since the 17th century, numismatists have observed two epochs on Sinope’s Roman period coin issues (e.g. Hardouin 1689: 140). There was the epoch of 45 BCE, perhaps the annus coloniae (e.g. RPC III 1229; cf. Augusta Emerita, Johnston 2017: 56-57 fn. 202-203; Abascal 2002: 284; Philippi AE 1932, 21; briefly Samos IG XII,6 1:187 l. 8-11), as it coincided with reports of a Caesarian colony (Strab. 12.3.11). Then there was the epoch of 70 BCE (e.g. RPC VI 6501), seemingly replacing the earlier epoch, but only from the early third century onwards (Kubitschek 1908: 68-71; Magie 1950: 342 no. 42). Neither changing epochs or the use of many epochs were rare phenomena. That said, known examples show cities replacing old epochs with those that commemorate new events and circumstances (Leschhorn 1993: 439-541). It is then odd for Sinope to abandon the epoch commemorating its colonial foundation in favor of an epoch 25 years earlier. Why? Leschhorn gave two potential scenarios: perhaps 70 BCE was the outcome a pro-Severan party defeating the old guard, or there was a “Gräzisierung" movement under which Sinope opted for a symbolically more acceptable epoch (Leschhorn 1993: 162), but these suggestions are limited by lack of evidence. This paper reassesses Sinope’s changing epochs with two approaches. First is a reframing of the Leschhorn’s assumed constitutional symbolism attached to the epoch of 45 BCE that leads to factionalism, and the “Roman” nature of Sinope’s so-called Kolonieära in Leschhorn’s alternative “Gräzisierung” thesis. The question asked here is whether Sinope had an established era system in place as part of its Hellenistic past. Sinope likely used the Pontic era while under Mithridatid control (Leschhorn 1993: 150). Recent discussions of stamped amphorae further indicates that the Seleucid era system was likely present if not also used at Sinope (Saprykin & Fedoseev 1999: 135-143). Further, we now have ceramic tiles time-stamped with a formula such as "s(aeculo) S(inopensis) (colonia) i(nducta) an(no) IV" (Fedoseev 2019: 16-17). If Fedoseev’s reading of the time-stamp is correct, we may consider the possibility that the saeculum Sinopensis was a system that could have accommodated multiple epochs, and the phenomenon in question was a symptom of an entrenched but adaptative time-reckoning mechanism at work. The second approach considers the epoch of 70 BCE regionally. This epoch was primarily used at Amastris, but also attested at Abonuteichos. Both cities were described by Roman authors as prosperous in their own ways (e.g. Luc. Alex. 9, 25; Plin. Ep. 10.98). Both cities also began to issue 3 to 4 units of local bronze coinage from the reign of Trajan onwards, including the 6-assaria, associated with economic prosperity (Zajac 2023: 30-32, Tab. 1a). Epigraphic and numismatic evidence further suggest that Amastrians were mobile across the Black Sea and the Aegean, some even serving as koinon officials of Bithynian and other regional koina (Marek 2003: 63-67). There is the possibility that Sinope changed its epoch to adhere to regional time-reckoning norms set by more dominant peers.